Perspektif Pendidikan Islam Terhadap Poligami - Malaka, Zuman (Jurnal Keislaman, 2024)
This article discusses the issue of polygamy from the perspective of Islamic education which includes the legal basis governing the practice of polygamy and the application of Islamic educational values ​​in the practice of polygamy. This research uses a type of library research, which is research related to reading, recording and managing materials used in activities related to research. The data collection technique uses library research. The research results show that basically polygamy can be carried out by applying the conditions regulated in the Al-Qur'an and positive law in Indonesia. In addition, by understanding and applying Islamic educational values ​​such as justice and responsibility, polygamous marriages can be carried out with full wisdom, justice and harmony in accordance with Islamic teachings. The values ​​in Islamic education create a strong foundation for building a balanced and sustainable family.